Further Examination of the Psychometric Properties of the Current Experiences Scale and Model of Resiliency - James Groves; Christina Luberto; Gregory Fricchione; Elyse Park (SAGE Publishing, 2022)
Background Stress-related disease is increasing, with high resilience proposed as protective. Whilst the Current Experiences Scale (CES) shows promise as a measure of resilience, its psychological correlates and relationship to psychological stress remain unclear. Objectives (1) Further explore the psychometric properties of the CES, (2) identify modifiable psychological factors associated with the CES and (3) test a previously published model for the influence of adaptive strategies and stress management factors on resiliency and stress. Methods N = 455 individuals (mean age = 47.8, 65.1% female) completed measures of adaptive strategies: mindfulness (Cognitive and Affective Mindfulness Scale-Revised), positive affect (Positive and Negative Affect Schedule) and gratitude (The Gratitude Questionnaire), stress management skills: coping (Measure of Current Status-A), depression (Patient Health Questionnaire-8) and anxiety (General Anxiety Disorder Assessment) and outcomes: resilience (CES) and stress (Perceived Stress Scale). Cronbach's alpha and confirmatory factor analysis (CFA) examined the psychometric properties of the CES. Multivariable regression identified psychological variables associated with resilience. Structural equation modelling (SEM) tested the previously published model for resilience. Results The CES and its subscales showed good internal consistency (ɑ = .75-.93). The 23-item CES produced excellent results for model fit (Root Mean Square Error of Approximation (RMSEA) = .07, Standardized Root Mean Square Residual (SRMR) = .06, Comparative Fit Index (CFI) = .99; Tucker-Lewis Index (TLI) = .99). Higher gratitude (P < .0001), mindfulness (P < .0001), positive affect (P < .0001) and coping (P < .0001) were associated with higher resilience. Depression (P = .23) and anxiety (P = .34) were not. A model of resilience which included gratitude, mindfulness, positive affect and coping as determinants of resilience and perceived stress performed well (RMSEA = .03, SRMR = .02, CFI = .99; TLI = .99). Conclusions The CES was validated in a large sample. The association of gratitude, mindfulness, positive affect and coping with resilience may guide practitioners seeking to design resilience-enhancing programs.